2016
DOI: 10.1021/acsinfecdis.6b00094
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiosis Drug Discovery: Opportunities and Challenges

Abstract: The apicomplexan parasite Cryptosporidium is the second most important diarrheal pathogen causing life-threatening diarrhea in children, which is also associated with long-term growth faltering and cognitive deficiency. Cryptosporidiosis is a parasitic disease of public health concern caused by Cryptosporidium parvum and Cryptosporidium hominis. Currently, nitazoxanide is the only approved treatment for cryptosporidium infections. Unfortunately, it has limited efficacy in the most vulnerable patients, thus the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 63 publications
1
48
0
Order By: Relevance
“…A very safe drug profile is thus a key component of the target product profile18,19. KDU731 has a selectivity index of more than 100 (CC 50 HepG2 = 15.6 μM and CpCPE EC 50 = 0.1 μM) (Extended Data Table 1).…”
Section: Pharmacokinetic Properties Of Kdu731mentioning
confidence: 99%
“…A very safe drug profile is thus a key component of the target product profile18,19. KDU731 has a selectivity index of more than 100 (CC 50 HepG2 = 15.6 μM and CpCPE EC 50 = 0.1 μM) (Extended Data Table 1).…”
Section: Pharmacokinetic Properties Of Kdu731mentioning
confidence: 99%
“…There are several constraints to drug development for cryptosporidiosis 4, 12 . The pathogenesis of the disease and the molecules and pathways that can be targeted for drug development are poorly understood 13 .…”
Section: Novel Cell Culture Models Enable Propagation Of Cryptosporidmentioning
confidence: 99%
“…Primary human and bovine IEC models permit infections and Cryptosporidium hominis and C. parvum , respectively 16, 17 , and C. parvum infection in a non-cancer-derived IEC line, FHs 74 Int, has also been reported 18 . However, these cell lines support C. parvum infection for only a few days, do not permit completion of the life cycle or continuous propagation 12 , and can display variation in gene expression depending on culture conditions 19 . Cell-free systems for C. parvum culture have been reported 20 , but although the parasite was observed to complete its life cycle by transmission electron microscopy 21 , these in vitro axenic systems do not permit investigations of the parasite interactions with the host epithelia.…”
Section: Novel Cell Culture Models Enable Propagation Of Cryptosporidmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the reported efficacy of nitroimidazole drugs, treatment failures in giardiasis occur in up to 20% of cases and a recent report from the Hospital for Tropical Diseases, London found that the nitroimidazole therapy failure rate in giardiasis was 40.2% in 2013 (Nabarro et al, 2015). Nitazoxanide, the only treatment option for cryptosporidiosis, has an efficacy ranging from 56% in malnourished children to 80% in healthy adults and it is not effective for immunocompromised patients (Manjunatha et al, 2016). All these factors make the development of new antimicrobials to treat these infections a critical need to avert future outbreaks and deaths.…”
mentioning
confidence: 99%